2013
DOI: 10.1111/ijfs.12432
|View full text |Cite
|
Sign up to set email alerts
|

The effect of storage on nutritional, textural and sensory characteristics of creamy ricotta made from whey as well as cow's milk and goat's milk

Abstract: The aim of this study was to develop a creamy ricotta using a mixture of goat and cow whey as the main ingredients, with the addition of whole goat and cow milk. The nutritional composition, texture and sensory characteristics of the ricotta cheese were evaluated over 14 days of refrigerated storage. There was a decrease in protein and ash content and pH changes during the assessed storage periods. The instrumental texture profile indicated that the creamy ricotta was easily deformable, with minimal inelastici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
35
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 48 publications
9
35
2
3
Order By: Relevance
“…Di Pierro et al (2011) obtained similar acidity results, from 0.26 to 0.34%, after 30 days of storage. Borba et al (2014) found no difference up to 14 days; it remained at 0.3%. This was attributed to the absence of starter culture in the manufacture of cheese that resulted in whey.…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…Di Pierro et al (2011) obtained similar acidity results, from 0.26 to 0.34%, after 30 days of storage. Borba et al (2014) found no difference up to 14 days; it remained at 0.3%. This was attributed to the absence of starter culture in the manufacture of cheese that resulted in whey.…”
Section: Resultsmentioning
confidence: 75%
“…The recoverable total solids content in cheeses is quite variable according to the origin of whey, milk proportion and characteristics of manufacturing technologies that influence yield (Hawkins et al, 2009). Borba et al (2014) found content of 24.05% for ricotta manufactured only with bovine whey and when milk is added, this content increased to 25.91%. Higher levels are found in ricotta prepared with goat milk whey (30.68%) (Pizzillo et al, 2005), or whey previously treated with calcium concentration or precipitation, which removes hydrophilic lipoproteins that reduce yield (Prudencio et al, 2014).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations